Impact of cascade reservoir on the sources of organic matter in sediments of Lancang river - Yufei Bao; Meng Sun; Yuchun Wang; Ji Lu; Yajie Wu; Hao Chen; Shanze Li; Yong Qin; Zhuowei Wang; Jie Wen; Xinghua Wu; Zhongjun Wang (iScience)
Summary: The construction of dams to intercept natural rivers constitutes the most severe human activity influencing the underlying surface. This study focuses on four cascade reservoirs of the Lancang River and explores their impact on the migration of organic matter in sediments. The research reveals significant spatial variations in total organic carbon (TOC) and total nitrogen concentrations in the sediments of the four reservoirs. The carbon and nitrogen isotopes indicate that terrigenous organic matter is the main source of TOC in the sediments, contributing an average of 66.80%. Endogenous algal-derived organic matter is the second significant source, contributing between 14.30% and 32.91%. The sources contributed from upstream organic matter are the lowest, ranging from 6.36% to 15.33%. Our study demonstrates that the construction of cascade reservoirs may significantly alter the processes of material sources in the river basin ecosystem, particularly in the large reservoir which increased more endogenous algal-derived organic matter.